Factors Determining Work Arduousness Levels among Nurses: Using the Example of Surgical, Medical Treatment, and Emergency Wards - Kowalczuk, Krystyna; Sobolewski, Marek; Krajewska-Kułak, Elżbieta (BioMed research international, 2019)
Introduction. Staff shortages among nurses have been severely felt in most countries around the world for many years. In Poland, this problem is particularly visible due to the lowest nursing employment rate per 1000 inhabitants among 28 EU states and the high rate of leaving the profession. The average age of Polish nurses has been constantly growing for several years—in 2016 it was 50.79, while in 2008 it was 44.19. These data confirm that young nurses are the first to leave the profession. Diagnosis of the working conditions and psychosocial burden level among nurses should be subject to detailed analysis, so that leaving the profession will not additionally deepen the difficult staffing situation in health care. Aim. The aim of the study was to identify factors affecting the assessment of work arduousness levels among nursing personnel. Materials and Methods. The study was conducted among 573 nurses working on surgical, medical treatment, and emergency wards. A standardized job evaluation questionnaire was used to conduct the survey. Results. (1) Stress levels depended on the ward in which the surveyed person worked. Nurses working in the emergency ward assessed their conditions the best, with the lowest stress. The average general result in this group was 38.1 points versus 46 and 45.7 points in the surgical and medical treatment wards, respectively. (2) At the level of the whole studied group, both the nurses’ age and work experience did not differ statistically significantly in the total assessment of working conditions. Differences in the assessment of work arduousness in different age categories occurred at the level of individual wards. In the surgical ward, younger employees were characterized by higher stress levels, especially in the area of arduousness (p=0.0165). In the medical treatment wards, there was a similar age-to-stress ratio for the area of organizational uncertainty (p=0.0063). With age, employees of the emergency ward became more indifferent to stress related to unpleasant working conditions (p=0.0009), while stress related to organizational uncertainty increased (p=0.0495). (3) Nurses working in managerial positions assessed the overall stress related to their job higher than other nurses. They were particularly at risk for burdens related to haste, responsibility, and organizational uncertainty. The average overall assessment of work arduousness for this group was 44.6 points, while for surgical nurses it was 37.2 points. Correlations between the performed function and stress levels were found for almost all of the studied work characteristics (except for hazards). (4) Education had a statistically significant impact on the perception of working conditions in several dimensions. The people with the lowest education evaluated working conditions the best. The difference between people with a higher and those with a secondary education with a specialization was definitely smaller and often nonexistent. Education differentiated the work arduousness assessment depending on the ward. The most statistically significant correlations were obtained in surgical wards, and the least in medical treatment wards. Conclusions. (1) The study results indicate the need to diagnose problems related to work conditions in the context of occupational stress within individual hospital wards. To limit employee turnover, nursing staff managers should approach the issue of improving working conditions individually for each ward, due to differences in the nature of the work and level of stressogenicity. (2) In each hospital ward, employees at different stages of their career are sensitive to the psychosocial burden resulting from different work characteristics. These areas should be thoroughly diagnosed and the burden minimized to prevent departures from the profession—at early stages of the professional career as well as among experienced personnel. (3) Nurses working in managerial positions should receive the necessary substantive support, due to the higher stress burden associated with greater responsibility.